Experience Developing a Community Pharmacy Practice-based Research Network - Margie E. Snyder; Caitlin K. Frail; Lindsey V. Seel; Kyle E. Hultgren (University of Minnesota Libraries Publishing, 2012)
In 2010, the Purdue University College of Pharmacy established the Medication Safety Research Network of Indiana (Rx-SafeNet), the first practice-based research network (PBRN) in Indiana comprised solely of community pharmacies. In the development of Rx-SafeNet and through our early project experiences, we identified several "lessons learned." We share our story and what we learned in an effort to further advance the work of the greater PBRN community. We have formed the infrastructure for Rx-SafeNet, including an Executive Committee, Advisory Board, member pharmacies/site coordinators, and Project Review Team. To date, 22 community pharmacies have joined and we have recently completed data collection for the network's first project. Lessons learned during the development of Rx-SafeNet may benefit PBRNs nationally. Although community pharmacy PBRNs are not yet commonplace in the U.S., we believe their development and subsequent research efforts serve as an important avenue for investigating medication use issues.   Type: Idea Paper